Notes on metropolitan Manila reorganization - Caoili, Manuel A. (1978)
Rapid urbanization, pressures of population growth and unabated expansion of economic activities in the Metropolitan Manila area were the raison d 'etre for the organization of the Metropolitan Manila Commission. The MMC politically integrates the four cities and thirteen municipalities located in the Metropolitan Manila area and serves as the area's decision making framework. Where previously, local services were provided solely by affluent- municipalities and autonomous cities or fully assisted by the national government subject only to the administrative jurisdiction of the provincial government concerned, the present MMC integrates the services common to the area such as transportation, garbage disposal/refuse management, health and social welfare and coordinates with local governments services like housing and resettlement, squatter relocation, parks and playground maintenance, education, family planning/population, nutrition, green revolution and sports development. While progress has been noted in the integration and coordination
activities of the MMC, it still has to undertake and accomplish the substantive integration of the local services, comprehensive area planning, and the standardization of the internal management and operation of lower-level local governments.
Keywords: Local governance; Local autonomy; Urbanization; Economic zoning; Metropolitan Manila Area